The Idea Itself and the Circumstances of Its Emergence as Predictors of New Product Success - Goldenberg, Jacob; Lehmann, Donald R.; Mazursky, David (Management Science, 2001)
In view of the distressingly low rate of success in new product introduction, it is important to identify predictive guidelines early in the new product development process so that better choices can be made and unnecessary costs avoided. In this paper, we propose a framework for early analysis based on the success potential embodied in the product-idea itself and the circumstances of its emergence. Based on two studies reporting actual introductions, we identified several determinants (such as how the ideas originated, their specific configurations, and the level of technology required for their implementation) that significantly distinguish successful from unsuccessful new products in the marketplace. We suggest that these factors, together with already known factors of success/failure, may aid in the estimation of the potential of a concept early in its development.